VD_FINDINFO Arrêt / 2023 / 65 vom 11. April 2023 - VD Tribunal cantonal (2023)
FORCE PROBANTE, ENQUÊTEEN GÉNÉRAL, MÉTHODE MIXTE D'ÉVALUATION, MESURE DE RÉINSERTIONART. 14A LAI, EXPERTISE PLURIDISCIPLINAIRE | 17 LAI, 28 LAI, 28a LAI, 29 LAI, 27bis RAI